Disappearing large calcified thoracic disc herniation in a patient with thalassaemia. (28th January 2016) - Ahmad, Faiz U; Schallert, Erica; Bregy, Amade; Post, Judith D; Vanni, Steven
Abstract : Regression of herniated disc fragments with subsequent improvement in clinical symptoms has been reported in the lumbar and cervical spine. Such regressions in the thoracic spine are extremely rare. We report a case of a 38-year-old patient with thalassaemia who had regression of a large calcified herniated thoracic disc causing cord compression, with subsequent herniation of a second calcified disc at a different level and discuss the possible aetiopathogenesis. This is the first such case reported in the thalassaemia population.